2001
DOI: 10.1088/0741-3335/43/12/304
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of edge localized modes in the TCV tokamak

Abstract: The D α emission time-series from the TCV tokamak was investigated for a large set of ELMy discharges, to determine whether fluctuations in the time delay between ELMs are the result of noise only, or whether a deterministic process in a chaotic state exists, as suggested by results on JT-60U (Bak et al 1999 Phys. Rev. Lett. 83 1339. This study was carried out by searching the time-series of each discharge for transient sequences that are generic to chaotic systems, called unstable periodic orbits (UPOs). By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 22 publications
3
47
0
Order By: Relevance
“…In magnetically confined fusion plasmas, edge localized modes (ELMs; see the top left panel of figure 1), whose characteristics are deeply linked to the overall confinement properties of the plasma, provide a well-defined dataset of pulsed events. The statistical properties of measured ELM sequences [7,27,28] should provide a rich field of research, shedding fresh quantitative light on plasma confinement. However, ELM measurements are challenging insofar as magnetically confined fusion plasmas are seldom quasistationary on timescales long enough to enable robust ELM statistics to be constructed.…”
Section: Statistics Of Pulsed Phenomena In Plasmasmentioning
confidence: 99%
“…In magnetically confined fusion plasmas, edge localized modes (ELMs; see the top left panel of figure 1), whose characteristics are deeply linked to the overall confinement properties of the plasma, provide a well-defined dataset of pulsed events. The statistical properties of measured ELM sequences [7,27,28] should provide a rich field of research, shedding fresh quantitative light on plasma confinement. However, ELM measurements are challenging insofar as magnetically confined fusion plasmas are seldom quasistationary on timescales long enough to enable robust ELM statistics to be constructed.…”
Section: Statistics Of Pulsed Phenomena In Plasmasmentioning
confidence: 99%
“…Characterization of the dynamics of ELMing processes via their quantitative statistical signatures is relatively novel. [8][9][10] It may also be informative to quantify, as here, the statistical signatures of correlation between ELMs and signals that capture global plasma dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative characterization of the dynamics of ELMing processes via their time domain properties, such as inter-ELM time intervals and ELM event waiting times, is relatively novel [10][11][12][13][14][15] and has provided evidence of unexpected structure in the sequence of ELM occurrence times. Recently, 16,17 we found that the signals from a system scale diagnostic, the toroidally integrating full flux loops in the divertor region of JET, contain statistically significant information on the occurrence times of intrinsic ELMs: the ELMs tend to preferentially occur when the full flux loop signals are at a specific analytic phase of their timeseries.…”
mentioning
confidence: 99%